AN ECOLOGY INTERVENTION IN AN ENGLISH STUDIES PROGRAMME: Contexts, Complexities and Choices - M. M., Padmakumar (Journal of Dharma, 2014)
Over the past few decades, there has been a critical mass gained regarding the need to engage purposefully with Ecology. Unfortunately, this has not provoked any stimulating work within the Humanities and Social Sciences academia. In fact, alongside growing realisations about the necessity to address Ecology, there is a glaring absence of any significant engagement. In response to such a vexing reality, the Department of English at Christ University chose to initiate an Ecological venture within its Honours programme. This paper captures – the vigorous debates it lit up, the tough choices that had to be made, and the promise it offers – that complex journey.